MODERNISASI ARSITEKTUR TRADISIONAL ISTANA DALAM LOKAL DI SUMBAWA (STUDI HISTORIS ARKEOLOGI) - Subari, Subari; Anwar, Anwar (Jurnal Ilmiah Mandala Education (JIME), 2021)
The traditional architecture of the Dalam Loka Palace in Sumbawa is a historical heritage that is stored in local culture as a royal residence. This palace was built in 1885 during the reign of Muhammad Jalaluddinsyah III which was used as a resting place for the royal family. The purpose of the research is to see the history and development of palace architecture along with the renovations that do not cause a shift in values, let alone cause the loss of meaning and social function as well as the local wisdom contained in it. The method used in this research is using a qualitative descriptive approach that starts from the stages of source collection (heuristic), criticism (verification), analysis and synthesis (interpretation), and writing (historiography), observation, interviews, literature study. The results show that the modernization referred to in the traditional architecture of the Istana Dalam Loka is to carry out a thorough restoration without changing the meaning as a moral basis that is embedded in the value of the existence of the palace in local Sumbawa.